Toward global scientific literacy: Evaluating primary science education in Indonesia’s Merdeka and Cambridge curricula - Wijaya, I Komang Wisnu Budi; Parwata, I Made Yoga; Indrawan, I Putu Oktap; Suparya, I Ketut (Indonesian Journal of Educational Development (IJED), 2025)
In response to global demands for 21st-century competencies, Indonesia has implemented the Merdeka Curriculum, while many internationalised schools adopt the Cambridge Curriculum. Both aim to foster scientific literacy but differ in philosophical foundations, curriculum structure, and pedagogical design. This study aims to compare the implementation of science education in these two curricula at SD Tunjung Sari, an SPK (Satuan Pendidikan Kerjasama) school in Bali, to identify their respective strengths and inform future curriculum integration. Employing a qualitative design, data were collected through document analysis, semi-structured interviews, and classroom observations. The study focused on four key components: learning objectives, content, instruction, and assessment, using Miles and Huberman’s interactive model. Findings indicate that the Merdeka Curriculum emphasises holistic development and contextual learning through project-based and Science–Technology–Society (STS) approaches. At the same time, the Cambridge Curriculum promotes inquiry-based learning with a structured, internationally benchmarked sequence. Although both curricula align with PISA’s scientific literacy domains, they differ in content scope and delivery. The study recommends a hybrid model that integrates global standards with local values to enhance science education in diverse contexts. This can support policymakers and educators in designing future-ready curricula that are both globally competitive and culturally rooted.